Bilateral Nasoalveolar Cyst Causing Nasal Obstruction - Uzeyir Yildizoglu; Fatih Arslan; Bahtiyar Polat; Abdullah Durmaz (Case Reports in Otolaryngology)
Nasoalveolar cysts, which originate from epithelial remnants of nasolacrimal duct, are nonodontogenic soft tissue lesions of the upper jaw. These cysts are thought to be developmental and are presented with fullness in the upper lip and nose, swelling on the palate, and sometimes nasal obstruction. Because of cosmetic problems, they are often diagnosed at an early stage. These lesions are mostly revealed unilaterally but also can be seen on both sides. In this case report, a patient who complained of nasal obstruction and then diagnosed with bilateral nasoalveolar cysts and treated by sublabial excision is presented and clinical features and treatment approaches are discussed with the review of literature.